Технологія влаштування несучих конструкцій перекриттів з окремих елементів способом «ОПОРИ-БАЛКА» - Савйовський, В. В.; Броневицький, А. П.; Савйовський, А. В. (Ways to Improve Construction Efficiency, 2014)
The features of device of new and strengthening of the existent ceiling are сonsidered in the conditions of reconstruction of building. The method of device of bearing elements of ceiling an offer method of "support - beam" is presented. The not necessity of simultaneous acceptance of structural and organizational technological decisions of implementation of construction-works is indicated taking into account the terms of reconstruction.